2020
DOI: 10.3989/scimar.05018.11b
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of the reef-building coral <em>Cladocora caespitosa</em> and the canopy-forming alga <em>Treptacantha ballesterosii:</em> Description of a new Mediterranean habitat

Abstract: Shallow Mediterranean rocky environments are usually dominated by macroalgae, but the stony colonial zooxan­thellate coral Cladocora caespitosa is able to build extensive banks in some particular areas. Although zooxanthellate corals and benthic macroalgae are expected to compete for light and space when overlapping in the same habitat, there is previous evidence that C. Caespitosa and Mediterranean macroalgae do not suffer from competitive exclusion when living together. Here we characterize a new and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The present study evaluated, for the first time, the biodiversity of the Graham, Nereo and Pantelleria Vecchia Banks located in the Strait of Sicily. The numerous banks in the area, and most of the shallower ones located in the euphotic zone (0-100 m), provide habitats for a large variety of species together with unique ecosystems, many of which are still to be discovered and described (Clark et al, 2006), as demonstrated by the newly reported Cladocora coespitosa-Treptacantha ballesterosii habitat (Pons-Fita et al, 2020). This also applies to the 'Corallium rubrum facies' observed on the Graham Bank, which would need a formal description prior to its possible inclusion in lists of marine habitats.…”
Section: Discussionmentioning
confidence: 99%
“…The present study evaluated, for the first time, the biodiversity of the Graham, Nereo and Pantelleria Vecchia Banks located in the Strait of Sicily. The numerous banks in the area, and most of the shallower ones located in the euphotic zone (0-100 m), provide habitats for a large variety of species together with unique ecosystems, many of which are still to be discovered and described (Clark et al, 2006), as demonstrated by the newly reported Cladocora coespitosa-Treptacantha ballesterosii habitat (Pons-Fita et al, 2020). This also applies to the 'Corallium rubrum facies' observed on the Graham Bank, which would need a formal description prior to its possible inclusion in lists of marine habitats.…”
Section: Discussionmentioning
confidence: 99%
“…The species is currently distributed throughout the entire Mediterranean basin as discontinuous and isolated colonies or, more rarely, as coral beds or banks ( Schiller, 1993 ; Peirano et al, 2004 ; Kersting and Linares, 2012 ; Chefaoui et al, 2017 ; López-Márquez et al, 2019 , 2021 ). Though numerous studies on the ecology and biological traits of C. caespitosa have been carried out ( Peirano et al, 2004 ; Kersting et al, 2013a , 2013b , 2014a , 2014b ; Rubio-Portillo et al, 2018 ; Pons-Fita et al, 2020 , among others), genetic connectivity studies of this species are scarce. Only three studies on the genetic differentiation of the species, all conducted at a regional scale, have been published: Casado-Amezúa et al (2014) studied the species in the western Mediterranean where they found low genetic connectivity related to sporadic dispersal events among the studied populations, almost the same results obtained in the eastern Mediterranean by López-Márquez et al (2021) .…”
Section: Introductionmentioning
confidence: 99%